The impact of cardiac rehabilitation on atrial fibrillation recurrence after pulmonary vein isolation: results of a large retrospective study - Önder, Rana; Geebelen, Gitte; Scherrenberg, Martijn; Dendale, Paul; Desteghe, Lien; Heidbuchel, Hein; Vijgen, Johan (Frontiers in Cardiovascular Medicine, 2026)
AimsPulmonary vein isolation (PVI) is a common treatment for atrial fibrillation (AF), but many patients experience recurrences. Physical activity can be beneficial in reducing recurrences. In Belgium, patients can join a reimbursed cardiac rehabilitation (CR) program after PVI, although not all do. This study retrospectively examined the impact of CR on AF recurrence after PVI.MethodsA database of AF patients who underwent primary PVI ablation between 2007 and 2020 was analysed for documented AF recurrences. Patients were retrospectively divided into control and intervention groups based on their participation in the CR program.ResultsOf 1,765 included patients, 1,177 were controls, and 588 participated in CR [median age 64 (56–70) years (p = 0.186), BMI 27.7 kg/m2 (p < 0.001), median follow-up 1,516 days (p < 0.001)]. The prevalence of hyperlipidemia (p = 0.009), smoking history (p = 0.001), and sleep apnea (p = 0.009) differed between both groups. Survival analysis showed no significant difference overall (p = 0.340), although there was an intriguing crossover of the recurrence curves after about 1,500 days. Despite an initial higher recurrence, patients who followed CR had a 32.2% lower odds of AF recurrence from 1 year post-PVI until study end (OR: 0.677 p = 0.005). After 3 months, BMI decreased significantly in the intervention group and increased in the control group (between-group p = 0.004).ConclusionOverall, we did not observe a lower AF recurrence in post-PVI patients with a CR program. Nevertheless, physical activity from the CR program may have long-term benefits based on weight loss and VO2 max increase.